Pabco Display Home
Pabco's Miniature Model Home is keyed to 1939 Living. With every fixture, every piece of furniture built to scale, it dramatically demonstrates how Pabco building materials can be used to build an inexpensive modernized home. It is part of the exhibit of The Paraffine Companies, Inc., in the Homes and Gardens Building at the Golden Gate International Exposition.